ON GENERALISATION OF GOMPERTZ-MAKEHAM DISTRIBUTION - Akinlolu Olosunde; Tosin Adekoya (Indonesian Journal of Statistics and Applications, 2020)
In this paper an exponentiated generalised Gompertz-Makeham distribution. An exponentiated generalised family was introduced by Codeiro, et. al., which allows greater flexibility in the analysis of data. Some Mathematical and Statistical properties including cumulative distribution function, hazard function and survival function of the distribution are derived. The estimation of model parameters are derived via the maximum likelihood estimate method.